Pendidikan Politik Sebagai Proses Belajar Membentuk Kesadaran Politik dan Peran Kewarganegaraan - Arlis Prayugo; Rahadi Budi Prayitno Prayitno (LP. Ma'arif Janggan Magetan, 2022)
The pursuit of political education for the general public and for educated people is to function in order to raise their awareness to be actively involved in controlling, evaluating, and increasing active participation in governance and the implementation of its policies. Political education is a continuous process, through political education that must be maintained is in shaping awareness in the role of human beings and the role of citizenship. This human role enables the development of talents and abilities of each individual, in carrying out his political functions in accordance with the status and mission of life that each individual has. While the role of citizenship invites the public to take an active role through participation in the process of thinking, dialogue and political action in order to achieve progress and improvement by realizing the role of their obligations and political rights.